The Value of helping : the story of Harriet Tubman - Johnson, Ann Donegan (La Jolla, CA : Value Comm, 1979)
Describes the helpful work of Harriet Tubman in aiding slaves to flee the South, in assisting the Union army during the Civil War, and in establishing homes for the old and needy after war.
Keywords: Tubman, Harriet, 1815?-1913; Afro-Americans -- Biography; Slavery in the United States -- Fugitive slaves; Helpfulness